PENGARUH PENGGUNAAN PLATFORM EDUKASI WORDWALL TERHADAP KEAKTIFAN SISWA KELAS V PADA MATA PELAJARAN BAHASA INDONESIA DI SD NEGERI 159 PALEMBANG - Triana, Okta; Ihwanah, Al; Fatimah, Siti; Boty, Middya; Dwi Saputra, Agra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The lack of students activity in the Indonesian language learning process is one of the problems found in grade V students. This study aims to determine the effect of the use of the Wordwall educational platform on the activeness of grade V students in Indonesian language subjects at SD Negeri 159 Palembang. This study uses a Quasi Experimental research type with a quantitative approach and a Nonequivalent Control Group Design. The population in this study was all grade V students, with the sampling technique using saturated sampling, so that the sample amounted to 43 students consisting of class V A as the experimental class and class V B as the control class. The research instrument used was a student activity questionnaire that had been tested for the validity of the data using validity and reliability. The data analysis technique uses normality tests and homogeneity tests, while the hypothesis testing technique uses the Independent Sample T-Test. The results of the study show that there is an influence of the use of the Wordwall educational platform on student activity. This is shown by the results of the hypothesis test with a significance value of 0.001 < 0.05, so that H0 is rejected and H1 is accepted. In addition, descriptively there was an increase in the average student activity in the experimental class from 82.29 to 92.29. Thus, it can be concluded that there is an influence of the use of the Wordwall educational platform on the activeness of grade V students in Indonesian subjects.